Analysis of Impact of Brand Marketing Strategies on Consumer Behavior in Malang City - Supriono; Sudarmiatin (Jurnal Ekonomi dan Bisnis Digital, 2023)
MSME is one sector that contributes to Indonesia's economic growth process. The condition of MSMEs in Indonesia is that there are around 40 million business actors in Indonesia, including MSMEs engaged in the culinary field. The aim is to identify marketing strategies carried out by culinary MSMEs in Malang Raya for the 2019–2022 period. This study uses a systematic literature review with the preferred reporting items for a systematic review and meta-analysis method. consisting of three empirical papers resulting from the 2019–2023 period published in the journal EMERALD. Results of this study indicate that there are keywords that provide updates from this research, such as brand awareness, loyalty, consumers, tourism, and the city of Malang as the object of this research.